Identification of LRP16 as a Negative Regulator of Insulin Action and Adipogenesis in 3T3-L1 Adipocytes - Zang, L.; Xue, B.; Lu, Z.; Li, X.; Yang, G.; Guo, Q.; Ba, J.; Zou, X.; Dou, J.; Lu, J.; Pan, C.; Mu, Y. (Hormone and Metabolic Research, 2013)
Leukemia related protein 16 (LRP16) was first cloned from acute myeloid leukemia cells in our laboratory. In the present study, we sought to investigate the role of LRP16 in insulin action and sensitivity, using LRP16-depleted and -overexpressing 3T3-L1 cells. LRP16 silencing resulted in a reduction of the expression and secretion of tumor necrosis factor-alpha (TNF-α) and a concomitant increase in the expression of peroxisome proliferator-activated receptor-gamma (PPAR-γ). Moreover, LRP16 depletion promoted insulin-induced glucose uptake and adipocyte differentiation of 3T3-L1 cells. In contrast, LRP16 overexpression increased TNF-α secretion, suppressed glucose uptake, and attenuated 3T3-L1 cell differentiation. The phosphorylation levels of insulin receptor substrate 1 (IRS-1), phosphatidylinositide 3-kinase (PI3-K), and Akt were increased in LRP16-deficient 3T3-L1 cells, and conversely, diminished in LRP16-overexpressing 3T3-L1 cells, when compared to the corresponding control cells. Additionally, LRP16 overexpression raised the phosphorylation level of mammalian target of rapamycin (mTOR). The pretreatment with rapamycin, a specific inhibitor of mTOR, prevented the TNF-α elevation and PPAR-γ reduction and restored the phosphorylation of IRS-1, PI3-K, and Akt in LRP16-overexpressing cells. Our data collectively indicate that LRP16 acts as a negative regulator of insulin action and adipogenesis in 3T3-L1 adipocytes, which involves the activation of the mTOR signaling pathway.
Keywords: leukemia related protein 16 (LRP16); insulin receptor substrate 1 (IRS-1); tumor necrosis factor-alpha (TNF-α); peroxisome proliferator-activated receptor-gamma (PPAR-γ); mammalian target of rapamycin (mTOR)